DETERMINANTS OF STOCK MARKET INVESTMENT INTEREST AMONG UNIVERSITY STUDENTS: EVIDENCE FROM MUHAMMADIYAH UNIVERSITY OF ACEH - Devi Pusfita; Zuraidah; Rusnaidi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of financial literacy, motivation, and information technology on investment interest in the capital market among students at Muhammadiyah University Aceh. The population in this study was all active students at Muhammadiyah University Aceh, totaling 3,118 students. The research sample consisted of 100 respondents selected using a sampling technique in accordance with the research criteria. The data used is primary data collected through questionnaires and tested using multiple linear analysis techniques. The results show that, partially, financial literacy affects investment interest and, partially, motivation and information technology do not affect students at Muhammadiyah University Aceh. In addition, simultaneously, the three independent variables affect investment interest among students at Muhammadiyah University Aceh. This study has practical implications for universities to strengthen financial education and literacy programs, particularly those related to the capital market.